Antigen-specific T cells and autoimmunity (2024)
Autoimmune diseases (ADs) showcase the intricate balance between the immune system's protective functions and its potential for self-inflicted damage. These disorders arise from the immune system's erroneous targeting of the body's tissues, resulting in damage and disease. The ability of T cells to distinguish between self and non-self-antigens is pivotal to averting autoimmune reactions. Perturbations in this process contribute to AD development. Autoreactive T cells that elude thymic elimination are activated by mimics of self-antigens or are erroneously activated by self-antigens can trigger autoimmune responses. Various mechanisms, including molecular mimicry and bystander activation, contribute to AD initiation, with specific triggers and processes varying across the different ADs. In addition, the formation of neo-epitopes could also be implicated in the emergence of autoreactivity. The specificity of T cell responses centers on the antigen recognition sequences expressed by T cell receptors (TCRs), which recognize peptide fragments displayed by major histocompatibility complex (MHC) molecules. The assortment of TCR gene combinations yields a diverse array of T cell populations, each with distinct affinities for self and non-self antigens. However, new evidence challenges the traditional notion that clonal expansion solely steers the selection of higher-affinity T cells. Lower-affinity T cells also play a substantial role, prompting the “two-hit” hypothesis. High-affinity T cells incite initial responses, while their lower-affinity counterparts perpetuate autoimmunity. Precision treatments that target antigen-specific T cells hold promise for avoiding widespread immunosuppression. Nevertheless, detection of such antigen-specific T cells remains a challenge, and multiple technologies have been developed with different sensitivities while still harboring several drawbacks. In addition, elements such as human leukocyte antigen (HLA) haplotypes and validation through animal models are pivotal for advancing these strategies. In brief, this review delves into the intricate mechanisms contributing to ADs, accentuating the pivotal role(s) of antigen-specific T cells in steering immune responses and disease progression, as well as the novel strategies for the identification of antigen-specific cells and their possible future use in humans. Grasping the mechanisms behind ADs paves the way for targeted therapeutic interventions, potentially enhancing treatment choices while minimizing the risk of systemic immunosuppression.